The Dynamics of Maritime Security along the South Western Coast of Cameroon 1981-2017: Manifestations and Challenges - Austine Laila; Nfi Joseph Lon (Researchparks Publishing, 2021)
Besides it’s strategic location in West and central Africa, the south western coastal region of Cameroon is endowed with numerous natural resources. Some of which include; a rich sub-soil, fisheries, touristic potentials, and petroleum deposits. These resources drew international attention thus culminating in to a huge maritime traffic along this corridor. From thence, Pirates took advantage and perpetrated criminal activities. From 1981, this maritime corridor therefore became a hot spot for all forms of maritime security threats. Based on this background, this piece attempts to unravel the plethora of maritime security threats that have plagued the south western coastal region of Cameroon over the years. The work argues that the state of Cameroon hitherto suffered from sea blindness but the upsurge of criminal activities in this zone pushed her into developing a maritime security strategy from the 1980s. As such, this piece launches an investigation in to 3 basic questions: what were these maritime security challenges that affected this region? What were the changing historical phases of these maritime security threats between 1981 and 2017, and how did these challenges manifest themselves along the region? To ensure a critical reflection on these interrogations, we exploit data from primary, secondary, and online sources. The paper concludes that the manifestations of these maritime security challenges posed a serious threat to national security, public health and the blue economy in general.